Letter from Carl D. Duncan to Patricia Whiting, January 19, 1966 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Duncan describes a conversation with a former student who is an abortion activist and mentions the results of his colonoscopy.